2019
DOI: 10.1101/581397
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

PERK inhibition mitigates restenosis and thrombosis - a potential low-thrombogenic anti-restenotic paradigm

Abstract: BackgroundDrug-eluting stents (DES) represent the main-stream management of restenosis following treatments of occlusive cardiovascular diseases. However, DES cannot eliminate instent restenosis yet exacerbate thrombogenic risks. To achieve dual inhibition of restenotic smooth muscle cell (SMC) de-differentiation/proliferation and thrombogenic endothelial cell (EC) dysfunction, a common target in both cell types, has been long-sought after. We evaluated the potential of protein kinase RNA-like endoplasmic reti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
20
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(20 citation statements)
references
References 52 publications
0
20
0
Order By: Relevance
“…Recently we developed local delivery platforms for lesiontargeted application of the first-in-class PERK inhibitor, GSK2606414, which demonstrated both anti-restenotic and anti-thrombotic efficacies in rodent models. 15 Despite the endothelium friendliness and benefits we observed in our previous studies, the exact impact of PERK inhibition on the endothelium regeneration process in vivo, or reendothelialization, remained unknown. Using the thermosensitive gel technology for perivascular local delivery, here we further determined the impact of PERK inhibition on reendothelialization after endothelium denudation in the rat balloon angioplasty model ( Fig.…”
Section: Perivascular Application Of a Perk-selective Inhibitor Promomentioning
confidence: 77%
See 4 more Smart Citations
“…Recently we developed local delivery platforms for lesiontargeted application of the first-in-class PERK inhibitor, GSK2606414, which demonstrated both anti-restenotic and anti-thrombotic efficacies in rodent models. 15 Despite the endothelium friendliness and benefits we observed in our previous studies, the exact impact of PERK inhibition on the endothelium regeneration process in vivo, or reendothelialization, remained unknown. Using the thermosensitive gel technology for perivascular local delivery, here we further determined the impact of PERK inhibition on reendothelialization after endothelium denudation in the rat balloon angioplasty model ( Fig.…”
Section: Perivascular Application Of a Perk-selective Inhibitor Promomentioning
confidence: 77%
“…In our most recent report, we used an unbiased highthroughput drug screening approach designed to identify a common target for SMC inhibition yet preservation of EC viability. 15 We found that three of the top-scored hits were inhibitors of PERK, which represents an ER stress response pathway. In a follow-up study, we found that PERK could be targeted to block both restenosis and thrombosis in rodent models.…”
Section: Discussionmentioning
confidence: 93%
See 3 more Smart Citations